Analisis Penerapan dan Korelasi Model Pembelajaran Kolaboratif Tipe Pembunuhan Terhadap Hasil Belajar Siswa SMA Jambi - Mahirullah; Sri Muslimatul Husna; Farida Adriani (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This study aims to determine the applicability of the MURDER type collaborative learning model and the relationship between the implementation of this model on student learning outcomes. Methodology: The design used in this study is the Mix Method. Sampling was carried out by purposive sampling in senior high school 4 Jambi City. The instrument used is the observation sheet and questions. Before the test was carried out, the questions were tried to determine the validity, difficulty level, discriminating power, and reliability of the questions. The prerequisite test used normality and homogeneity tests, while the analysis used Bivariate and Pearson correlation. Main Findings: The results of this study indicate that the implementation of the model by teachers and students through qualitative results is exemplary, with an average quantitative result each for teachers is 78.125% and for students is 70.29%, followed by an average student learning outcomes that reach 75,26. The result of the correlation test is R = 0.717 with a significance value of 0.000 <0.05, which means that there is a significant correlation, while the contribution of the R Square value is 0.514, which means that the implementation of the MURDER type collaborative learning model, contributes to Learning Outcomes of 51.4 %. Novelty/Originality of this study: The novelty of this study is the focus on analyzing the application of the MURDER type collaborative learning model and determining its correlation to student learning outcomes at senior high school 4 Jambi City on the subject of reaction rates.